The relationship between gross domestic product (gdp) growth and foreign direct investment in Indonesia 2010-2023 - Wahyuliana, Eka; Ruslan, Nur Jaya Baiduri; Suhartini, Suhartini; Ansar, Ansar (Enrichment : Journal of Management, 2025)
This study aims to analyze the relationship between Gross Domestic Product (GDP) growth and Foreign Direct Investment (FDI) in Indonesia from 2010 to 2023. The research employs a descriptive quantitative approach using secondary data from the Central Bureau of Statistics (BPS) and other relevant institutions. The analysis reveals a positive long-term relationship between FDI and GDP growth. Although in certain periods an increase in FDI was not immediately followed by a surge in economic growth, the data generally indicate that FDI has a significant contribution to GDP growth, especially when directed toward strategic sectors. The study also finds that the effectiveness of FDI in promoting economic growth is strongly influenced by factors such as infrastructure quality, macroeconomic stability, and supportive investment regulations. These findings are consistent with previous studies that emphasize the importance of the domestic environment in maximizing the benefits of FDI. Therefore, appropriate policies are needed to enhance investment competitiveness and optimize the positive impact of FDI on national economic development